STRATEGI BELAJAR KITAB ARAB MELAYU DALAM MENINGKATKAN KEMAMPUAN LITERASI SANTRI DAYAH NAJMUL HUDA ACEH - Nuruzzahri (Indonesian Journal of Islamic and Social Science, 2023)
Over time, almost all in Indonesia have developed various teaching methods, especially in Arabic-Malay subjects. With the method It is hoped that students can more easily understand what is conveyed by Ustadz / Ustadzah during learning activities. Therefore, This study aims to describe the Arabic-Malay teaching methods in aceh. This is the formula the problem in this thesis is what method is used by Ustadz/Ustadzah on Malay Arabic subjects in Aceh, what are the obstacles to using teaching methods in Arabic Malay subjects in Aceh and how it is affected application of teaching methods to Arabic-Malay subjects in = Aceh. This research is research qualitative descriptive. Data was collected through observation, interviews and documentation. The research results obtained that the method used by Ustadz/Ustadzah in Malay Arabic subjects in Aceh is a method of question and answer, discussion, talaqqi, and giving task. Meanwhile, the obstacle often experienced by Ustadz/Ustadzah in Aceh lies in the students who are not yet able to do so Recite. The effect of applying the method is very good, that is can be seen in the high enthusiasm and enthusiasm of the students towards learning Malay Arabic Book.